The effect of the context in the rotation of the actual formulas and the determination of the grammatical time. - Mohammad, Maaz (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with the role of the context in the rotation between the actual forms of past, present and future, time is often divided into past, present and future formulas, the research examines the contexts that leads the original time from its position to another time that does not indicate it in the first place that shows that there is a difference between the temporal time and the grammatical, the research shows that the formula of the present verb is different from that of the past because of the existence of a presumption function and repent formula of the past about the present and future, which does not indicate by the origin of the past but the present time and future, so the context determines the grammar time.